Diagnostic Test of Transforming Growth Factor-Beta 1 (TGF-β1) in Menstrual Blood with Endometriosis - Kemas Yusuf Effendi; Excellena Nasrul; Iskandar Zulqarnain; null Theodorus; Rizani Amran; Heriyadi Manan; Adnan Abadi; Fatimah Usman; Cindy Kesty (Obstetrics and Gynecology International)
Background. Endometriosis is a benign disorder that is generally defined as the presence of endometrial glands and stroma outside their normal location. TGF-β1 is found in stromal cells and its expression is increased in epithelial cells of endometriotic cysts. Endometriosis diagnostics take a long time, so new markers are needed to diagnose endometriosis. This study aims to determine the diagnostic value of TGF-β1 in menstrual blood in diagnosing endometriosis. Method. Diagnostic tests to compare eutopic endometrial TGF-β1 levels from menstrual blood of patients with suspected endometriosis were undertaken in the Obstetrics and Gynecology Department of Dr. Mohammad Hoesin General Hospital, Faculty of Medicine, Sriwijaya University, Palembang, from July 2019 to November 2020. 50 patients who were suspected with endometriosis met the inclusion criteria. Comparison of TGF-β1 levels between endometriosis and nonendometriosis patients was analyzed using the Mann–Whitney test. The cutoff point of the TGF-β1 level towards the histopathological outcome was obtained using the ROC curve. Data analysis was performed by using SPSS version 22.0. Results. In this study, endometriosis patients were 31.6 ± 6.55 years of age with a range of 20 to 46 years. In statistical analysis, there was no difference in BMI (p=0.181) and BMI classification (p=0.207), the history of contraception (p=0.097), infertility (p=1.000), and dysmenorrhoea (p=1.000) between endometriosis and nonendometriosis patients. In the study, there were differences in TGF-β1 between endometriosis and nonendometriosis patients (p≤0.001). By using the ROC curve, the cutoff point for TGF-β1 levels has the best sensitivity and specificity, which is 515 ng/ml. The TGF-β1 level has a sensitivity of 80%, a specificity of 90%, a positive predictive value (PPV) of 0.969, a negative predictive value (NPV) of 0.529, a positive likelihood ratio of 8, a negative likelihood ratio of 0.222, and an accuracy of 0.820 to the endometriosis outcome. Conclusion. It can be concluded that the TGF-β1 level has a very good diagnostic value in establishing endometriosis diagnostics. This trial is registered with ISRCTN72218532.